Dari Dapur Lokal ke Pasar Digital: Strategi Pemasaran Kuliner UMKM di Era Ekonomi Kreatif (Jurnal Manajemen Bisnis Digital Terkini, 2026)
The rapid growth of the creative economy, particularly in the culinary subsector, has prompted micro, small, and medium enterprises (MSMEs) to adopt digital marketing strategies as a means to enhance competitiveness and expand market reach. This study employs a systematic literature review (SLR) approach with content analysis to map key concepts, identify research gaps, and explore future research directions concerning the transformation of culinary MSMEs from local kitchens to digital markets. Findings reveal that organizational learning mediated by motivation, culture, leadership, and continuous digital marketing practices plays a pivotal role in this transformation. However, significant research gaps persist, including limited longitudinal studies, inadequate integration of organizational culture and leadership into digital marketing frameworks, and insufficient comparative analyses across diverse MSME profiles. This study contributes theoretically by synthesizing fragmented literature on culinary marketing in the digital creative economy and offers practical insights for MSME actors, mentors, and policymakers in designing adaptive and sustainable digital marketing strategies.